Influence of plaque morphology on the mechanism of luminal enlargement after directional coronary atherectomy and balloon angioplasty. Issue 2 (August 1995) - Marsico, F.; Kubica, J.; De Servi, S.; Angoli, L.; Bramucci, E.; Costante, A. M.; Specchia, G.
Abstract : OBJECTIVE--To relate the mechanism of luminal gain after directional atherectomy and balloon angioplasty to the morphological characteristics of the coronary lesions, assessed by intravascular ultrasound imaging. DESIGN--Intravascular ultrasound imaging was performed before and after the revascularisation procedure to assess the contribution of wall stretching and plaque reduction in luminal gain. SUBJECTS--32 patients undergoing balloon angioplasty and 29 undergoing directional coronary atherectomy. MAIN RESULTS--The main luminal area in vessels treated by balloon angioplasty increased from 1.51 (SD 0.30) to 3.91 (1.09) mm2 (P < 0.0001) with a concomitant increase in total vessel area from 11.44 (2.73) to 13.07 (2.83) mm2 (P < 0.0001). Therefore stretching of the vessel wall accounted for 68% of the luminal gain while plaque reduction accounted for the remaining 32%. This mechanism ranged from 45% in non-calcific plaques to 81% in echogenic plaques. The main luminal area in vessels treated by directional atherectomy increased from 1.49 (0.32) to 4.68 (1.73) mm2 (P < 0.0001), with a concomitant increase of total vessel area from 13.61 (4.67) to 15.2 (4.04) mm2 (P = 0.006). Thus stretching of the vessel wall accounted for 49% of the luminal area gain and plaque reduction for the remaining 51%. The presence of calcium influenced the relative contribution of these two mechanisms to the final luminal gain after directional atherectomy, since in calcific plaques stretching of the vessel wall accounted for only 9% of the luminal gain as compared to 56% in non-calcific plaques. After balloon angioplasty there was greater evidence of coronary dissections (32% v 3% after directional atherectomy, P < 0.01) and plaque fissure (60% v 0%, P < 0.01). Plaque fissure was more frequently seen in echolucent and concentric lesions, whereas dissections prevailed in echogenic and eccentric lesions. CONCLUSIONS--Intravascular ultrasound imaging may allow the assessment of acute changes in lumen and vessel wall after revascularisation procedures, and help in evaluating the potential effect of the structure and morphology of coronary lesions on the mechanism of luminal enlargement.